Bioacumulación de metales pesados (Pb, Hg,Cd) en el Bivalvo anaciara tuberculosa en cuatro localidades (bajo alto, estero Huayla , Puerto Hualtaco y Archipiélago de Jambelí) de la región costera de la provincia de El Oro.2014. - Ordoñez Lucin, Maria del Cisne (2015)
The present investigation concerns the bioaccumulation of heavy metals in bivalves Anadara tuberculosa at four locations in the Coastal Region of the Province of El Oro, which is described to the pollution that exists in the marine biota. The Coastal Region of the Province of El Oro has been a great deal of pollution, because the persistence of the heavy metals cause a great impact on the environment because they are not biodegradable and have a potential to bioaccumulate in living organisms.